SÍNTESE E CARACTERIZAÇÃO DE PORFIRINAS POLARES VISANDO A OBTENÇÃO DE COMPOSTOS HIDROFÍLICOS - Jesus, Daniel Rodrigo Pereira de (2011)
Porphyrins and its derivatives are of significant importance due to their physical, chemical and essential biological properties. The uses of porphyrins and metalloporphyrins include: photodynamic therapeutics; oxidation catalysts; components of printing inks and toners; and protective coatings. In addition, in the past few years, there has been extensive use of porphyrins in molecular electronics and other new materials. Such importance has prompted extensive studies on the synthesis of porphyrins. Therefore, the study on synthetic methods to improve the yields of porphyrins is of great significance. In this work some porphyrins were synthesized, with emphasis on water-soluble compounds. It was based on the classical Adler-Longo method and some modifications were made which led to yields 50% higher than those described in literature for some precursors of cationic and anionic compounds. For instance, DMAPP 37 lead to cationic metalloporphyrin 34 which is more water-soluble than the correspondent free base porphyrin, which will allow further research of toxic effects of hydrophilic porphyrins on microorganisms. Synthesized compounds.